Effect of Soil Texture on the Productivity of Two Shallot Varieties - Razali; Nasution, Zulkifli; Rahmawaty; Hanum, Chairani (Talenta Publisher, 2023)
The Lake Toba Catchment Area (LTCA) has long been known as a producer of shallots in North Sumatra. The Samosir variety is the mainstay local variety of the farmers. Due to the lack of quality seeds and disease attacks on the Samosir variety, farmers began to cultivate the Bima Brebes variety. This study aims to prove the difference in productivity of shallot varieties Samosir and Bima Brebes cultivated in the LTCA region by considering soil texture as a factor affecting productivity. This study was conducted in 6 shallot producing districts included in the LTCA. For analysis, 30 samples were selected based on the level of shallot productivity, with details of 10 low category production (< 4.5 tons/ha), 10 medium category production (4.5-7.5 tons/ha), and 10 high category production (> 7.5 tons/ha), along with the results of soil texture analysis. Correlation analysis was conducted to find the type of soil fraction that influenced productivity. ANCOVA to analyze the relationship between soil fraction and shallot productivity in each variety and analyze the difference in the productivity of Samosir and Bima Brebes shallots. The results showed that the sand fraction had an effect on shallot productivity in LTCA. The shallot cultivation land in LTCA has a sand fraction of 69-76% (sandy loam texture), where the greater the percentage of sand fraction, the higher the productivity of both shallot varieties. There was no difference in the productivity of Samosir and Bima Brebes shallots varieties. Bima Brebes variety can be a substitute seed for shallot cultivation in LTCA.